Christelik-nasionale onderwys in die nuwe Suid-Afrika - Westhuizen, H. G. van der (Hervormde teologiese studies, 1991)
Christian national education in the new South Africa The Dutch Reformed Church of Africa (Nederduitsch Hervormde Kerk van Afrika), as a People’s Church, according to Scripture takes an intense interest in the education of the nation’s youth. According to educational principles, the best school is one in own cultural milieu. The negative reports on multicultural education received from various countries are disquieting for the Church. Consequently, it is necessary to contemplate different options for maintaining Christian national education in a new era.